Pengaruh Perceived Discrimination terhadap Psychological Well-Being dengan Self-Esteem sebagai Mediator: Studi terhadap Pekerja dengan Preferensi Seksual LGBT di DKI Jakarta - Aditya Rifkian Amalif; Mira Sekar Arumi (Jurnal Ilmiah Psikologi MIND SET, 2022)
This study aims to determine the effect of perceived discrimination to the psychological well-being of workers with LGBT sexual preferences in DKI Jakarta and whether self-esteem impacts this effect. Respondents in this study consisted of 90 people consisting of 9 people with lesbian sexuality, 29 homosexuals, 30 bisexuals, and 22 transgenders. The method used in this study is a quantitative method that examines the effect of two independent variables on one dependent variable. Based on the results of the regression analysis test, it is known that perceived discrimination has a negative effect on psychological well-being (t = -9,795; p <0,005), meanwhile self-esteem has a positive effect on psychological well-being (t = 10,902; p < 0,05). This result proves the assumption that perceived discrimination can decrease, while self-esteem can increase workers' psychological well-being with LGBT sexual preferences in DKI Jakarta. Meanwhile, the analysis process from Hayes (2017) using SPSS obtained equally significant results, both in the total calculation and the direct effect, indicating that self-esteem partially mediates the effect between perceived discrimination and psychological well-being.